Propuesta de un nuevo diseño de programación en planificación de los servicios de salud en el hospital i essalud florencia de mora. año 2003 - Miranda Saldaña, Gilbert Segundo (2005)
With the objective to propose a new design to plan the attention in the services of Hospital I of the Social Insurance of Health, this one work in the Hospital I EsSalud of Florence of Mora from Trujillo-Peru was carried out the year 2003. The mentioned institution follows the programming system traditional using data taken from the previous year, such that projected the following year without obtaining real beneficial effects. If we used the proposed system, basing to us on data programmed at the beginning of the year, in a determined population, by means of the implementation of a computerized simple model in a spreadsheet of the Program of Microsoft Excel in relation to the index of real growth, we will obtain a change in the planning of the services of health that offers the Hospital I EsSalud real and significant advantages, in the time and its administration, surpassing comparativily to the traditional system.